Proteins Are Well-Preserved in Shells Toasted at 300°C Revealed by Proteomics - Ji, Xin; Huang, Jingliang; Wang, Zhenglu; Xu, Zhiqiang; Liu, Chuang (Frontiers in Marine Science, 2022)
The development of protein anti-degradation strategies is important for storage at ambient conditions, for example in vaccine storage. Despite that it is known that biominerals, typical inorganic-organic composites, can preserve proteins at room temperature for a long time, it is unclear the extent of protein degradation under high temperatures. In this study, we examined remaining proteins in the toasted abalone shell under high temperatures (200 and 300°C) by biomineral proteomics method. Surprisingly, 21 proteins including carbonic anhydrase, hemocyanin, actin can still be identified from shells even after toasting under 300°C, not much decreased compared to that in the 200°C-treated and the native shell. However, the microstructure and composition (both mineral and organic matrix) of shells were altered significantly revealed by scanning electron microscopy, infrared spectroscopy, and X-ray diffraction. The well-preserved proteins may be partially due to the sacrifice of mineral/organic interfaces and the formation of nanopores in the shell at high temperatures. Moreover, the extracted proteins from both groups were able to affect calcium carbonate in vitro, indicating certain remaining bioactivities of proteins. This study has potential implications in various fields such as protein storage at high temperatures and palaeoproteomics.